Bioassay-guided isolation of anti-inflammatory O-sulfated withanolides from Acnistus arborescens (Solanaceae) - Steinbrueck, Clara (2019)
Bioassay-guided fractionation of Acnistus arborescens (Solanaceae) organic extract afforded two anti-inflammatory withanolides: 2,3-Dihydro-3β-O-sulfate withacnistin (1) and 2,3-Dihydro-3β-O-sulfate withaferin A (2) showing IC50 values of 1.0 ± 0.1 and 14 ± 1 μM respectively in a LPS-stimulated RAW 264.7 murine macrophage assay. These compounds were also evaluated against two selected cancer cell lines showing significant cytotoxicity. Although there are several reports dealing with the chemistry of this species, we report for the first time the isolation of O-sulfated withanolides.